2011
DOI: 10.1017/s1474746411000297
|View full text |Cite
|
Sign up to set email alerts
|

Conditionality and Homelessness Services; ‘Practice Realities’ in a Drop-in Centre

Abstract: This article provides insights into the client−practitioner interaction, as understood through the eyes of those working at the front-line in a Drop-in Centre for homeless clients. Through a case-study analysis of 'official' techniques and informal approaches, it is argued that conditional practices are present in contemporary support practices. However, the picture is fragmented, with practitioners arguing for, but also deviating from, conditional strategies that aspire to shape client behaviour. Choices abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Similarly, Housing First projects which provide rapid access to independent housing with wraparound support to homeless people with complex needs (Homeless Link, 2016;Pleace, 2016;Tsemberis, 2010) arguably represent a meld of: persuasion, wherein staff proactively motivate clients to progress through the stages of recovery from addiction; bargaining, this being the 'immediate' offer of an independent tenancy direct from the street thereby negating the need for a prolonged hostel stay; and tolerance, that is, provision of long-term support which is not conditional on engagement with treatment plans (Tsemberis, 2010). Previous research has also demonstrated that frontline workers may oscillate between 'therapeutic' and 'disciplining' methods given the challenges they are faced with in the course of their day-to-day work (Dobson, 2011). These complexities do not, to our mind, negate the relevance of a clear conceptual framework within which to consider the meaning, impact and ethical implications of these distinctive mechanisms of control.…”
Section: Concluding Reflectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Housing First projects which provide rapid access to independent housing with wraparound support to homeless people with complex needs (Homeless Link, 2016;Pleace, 2016;Tsemberis, 2010) arguably represent a meld of: persuasion, wherein staff proactively motivate clients to progress through the stages of recovery from addiction; bargaining, this being the 'immediate' offer of an independent tenancy direct from the street thereby negating the need for a prolonged hostel stay; and tolerance, that is, provision of long-term support which is not conditional on engagement with treatment plans (Tsemberis, 2010). Previous research has also demonstrated that frontline workers may oscillate between 'therapeutic' and 'disciplining' methods given the challenges they are faced with in the course of their day-to-day work (Dobson, 2011). These complexities do not, to our mind, negate the relevance of a clear conceptual framework within which to consider the meaning, impact and ethical implications of these distinctive mechanisms of control.…”
Section: Concluding Reflectionsmentioning
confidence: 97%
“…England provides a particularly appropriate context within which to explore these perspectives and complexities given that, from the 1990s onwards, sharply increased levels of social control have been apparent in attempts to combat what Government has branded an 'anti-social street scene' , associated with activities such as begging and street drinking (Johnsen & Fitzpatrick, 2007). Moreover, and in concert with a broader 'responsibilisation' agenda aimed at 'welfare recipients' as a whole (Clarke, 2005), eligibility for support from homelessness service providers has become more explicitly tied to compliance with conduct-related conditions and 'engagement' with the help on offer (Dobson, 2011). In the most recent period, however, there has been something of a nascent swing back towards less conditional interventions for the subgroup with the most severe substance misuse and/or mental health problems (CLG, 2015;Terry & Cardwell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Engagement in transgressive 'street culture' activities associated with rough sleeping, such as begging and street drinking (McNaughton Nicholls, 2009;Fitzpatrick et al, 2011), has increasingly been the focus of 'control' as well as 'care' measures that seek to foster engagement with support services and desistance terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0047279417000289 from these activities (Dobson, 2011(Dobson, , 2015Fitzpatrick and Johnsen, 2009;Johnsen et al, 2016;Midgley, 2016).…”
Section: Conceptualising and Evaluating Interventionism In Homelessnementioning
confidence: 99%
“…This resistance stems from recognition of the difficulties that clients with complex needs face in adhering to behavioral conditions, and the negative impact that sanctions can have on their already precarious lives (Parr, ). This leads to the (partial) eschewal of conditionality in favor of a greater focus on the support needs of vulnerable clients, and a more tolerant approach to dealing with problematic behaviors, such as substance misuse or antisocial behavior (Dobson, ; Parr, ).…”
Section: Bureaucratic Encounters Under Neoliberalismmentioning
confidence: 99%
“…In recent decades, this neoliberal mode of bureaucratic engagement has come to dominate state provision across a variety of domains (Wacquant, ). However, recent research in the housing domain points to a potential shift away from neoliberal practices towards a renewed focus on unconditional care and support, at least for those clients deemed “high needs” (Dobson, ; Parr, ; Power & Bergan, ). This emergent approach recognizes the difficulties that clients with high needs face in adhering to entrepreneurial norms and behavioral conditions, and how this contributes to their marginalization.…”
Section: Introductionmentioning
confidence: 99%